DESIGNING AN ACCOUNTING SYSTEM FOR MUGUNGHWA BATAM - Ivone Ivone; Diana Diana (ConCEPt - Conference on Community Engagement Project, 2022)
The accounting system designed has made for Mugunghwa Batam in order to being able assist Mugunghwa Batam in doing their record by inputing the operational cost transactions. In the past, Mugunghwa Batam has simple accounting system by doing a manual book keeping.Activity on Mugunghwa Batam was implemented from September 2021 to December 2021. The methods used in this system were interviews, observation, design, and implementation. The accounting system is designed by using Microsoft Access. Where the system can display the output of financial reports in the form of balance sheet, income statements, debt reports, account receivable reports, sales reports, purchase reports, and inventory records based on the need of Mugunghwa Batam.The implemented accounting record system can be able to assist business owner in doing their recording of daily transactions so that to prevent inconsistencies or errors that caused by human error and can be identified clear and accurate based on financial reports. The results of financial statements that presented can be able to help business owners of being more selective in making their decisions that are right on target so that the business can develop for the better business. Recommendations for future is to add other features that can help the store and business owners.